Coping with Climate Change in the Sundarbans : Lessons from Multidisciplinary Studies - Dasgupta, Susmita; Wheeler, David; Sobhan, Md. Istiak; Bandyopadhyay, Sunando; Nishat, Ainun; Paul, Tapas (Washington, DC: World Bank, 2020)
Climate change poses serious threats to inclusive economic progress and poverty reduction. Strong countermeasures are required to increase the capacity of low-income people to mitigate their risk exposure to the impacts of climate change. Central pillars in planning for sustainable development and poverty alleviation must include vulnerability assessments, appropriate adaptation measures, and resilience-smart investments. This means placing climate change adaptation and resilience at the center of overall development policy. Coping with Climate Change in the Sundarbans contributes to this effort by synthesizing multiyear, multidisciplinary climate change studies on the Sundarbans—the world’s largest remaining contiguous mangrove forest and wetland of international importance, as well as home to some of South Asia’s poorest and most vulnerable communities. The studies’ findings indicate that, in a changing climate, sea-level rise, storm-surge intensification, and water salinization will alter the Sundarbans ecosystem significantly. The ripple effect of these changes will have multifaceted adverse impacts on the nature-dependent livelihoods, health, and nutrition of nearby communities. Elevated health risks, reduced land and labor productivity, and increased exposure to storms, floods, droughts, and other extreme events will make escape from poverty more difficult. Families in the Sundarbans are on the front line of these changes. Their experience and adaptation signal future decisions by hundreds of millions of families worldwide who will face similar threats from progressive sea-level rise. This research lays the technical foundation for developing a better understanding of the changes the Sundarbans currently faces, including responses of the ecosystem and human communities. Based on field research, location-specific, resilience-smart adaptation measures are recommended for reducing climate change vulnerability. Beyond the Sundarbans, the studies’ methods and findings will be of interest to development practitioners, policy makers, and researchers focused on island nations and countries worldwide that feature high-density populations and economic activity in low-lying coastal regions vulnerable to sea-level rise.